Nurses experience in emergency management in coastal area of Tarakan, North Borneo - Pujianto, Ahmat; Ose, Maria Imaculata; Lesmana, Hendy; Losong, Aprilisya Nensyiawati (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: The high prevalence of cardiovascular disease and lack of adequate health services can have an impact on the high number of emergencies in coastal communities. The condition of health services in coastal communities which the number of health workers, especially nurses is still limited, it becomes important to carry out research related to the experience of nurses in the treatment of emergencies in coastal areas.Objective: This study aims to identify the nurse’s experience of emergency management in coastal areas.Methods: This research was qualitative with a phenomenological design which involved eight participants of nurses who work in the primary healthcare in the coastal area. The data from the interview results was converted into audio files, and then transcribed and analyzed using content analysis manually.Results: There were three main themes of this study including emergency cases that have been handled by nurses at the coastal health center, the competence of nurses in emergencies care, the inhibiting factors of emergencies care at the coastal areas.Conclusion: Emergency management in coastal areas needs to be supported by several factors, including the fulfillment of health care facilities and the improvement of the nurse competencies